2016
DOI: 10.1016/j.hkjot.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Purposeful Activity in Psychiatric Rehabilitation: Is Neurogenesis a Key Player?

Abstract: Adult neurogenesis, defined as the generation of new neurons in adulthood, has been a fascinating discovery in neuroscience, as the continuously replenishing neuronal population provides a new perspective to understand neuroplasticity. Besides maintaining normal physiological function, neurogenesis also plays a key role in pathophysiology and symptomatology for psychiatric conditions. In the past decades, extensive effort has been spent on the understanding of the functional significance of neurogenesis in psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Social isolation is one of the environmental factors that exacerbate depression (Sharp and Lipsky, 2002 ). This was supported by a long-term follow-up study in which patients with social isolation demonstrated a high risk of recurrent depressive episodes (Riise and Lund, 2001 ), while social interaction was reported to facilitate recovery from depression (Cheung et al, 2016 ). For rodents, being a social species, social isolation is regarded as a potent stressor for inducing physiological changes which include alterations in learning, aggression and reduced body weight (Beery and Kaufer, 2015 ).…”
Section: Introductionmentioning
confidence: 87%
“…Social isolation is one of the environmental factors that exacerbate depression (Sharp and Lipsky, 2002 ). This was supported by a long-term follow-up study in which patients with social isolation demonstrated a high risk of recurrent depressive episodes (Riise and Lund, 2001 ), while social interaction was reported to facilitate recovery from depression (Cheung et al, 2016 ). For rodents, being a social species, social isolation is regarded as a potent stressor for inducing physiological changes which include alterations in learning, aggression and reduced body weight (Beery and Kaufer, 2015 ).…”
Section: Introductionmentioning
confidence: 87%
“…Adult neurogenesis abnormalities play an important role in a variety of neurodegenerative disorders, such as Alzheimer’s disease (AD), Huntington’s disease (HD), and Parkinson’s disease (PD) ( Winner and Winkler, 2015 ; Horgusluoglu et al, 2017 ; Berger et al, 2020 ). In addition, adult neurogenesis is associated with emotional illnesses, such as depression ( Sahay and Hen, 2007 ; Vaidya et al, 2007 ; Berger et al, 2020 ) and anxiety ( Cheung et al, 2016 ; Toda and Gage, 2018 ). Stress ( Odaka et al, 2017 ; Schoenfeld et al, 2017 ) and stroke ( Rahman et al, 2021 ) are also associated with abnormal adult neurogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations indicated that CRT could decrease frontal lobe dysfunctions and promote related cognitive functions in patients with schizophrenia. Psychiatric rehabilitation treatments, such as cognitive tasks, can lead to neurogenesis and the amelioration of various brain functions (Cheung et al, 2016).…”
Section: Introductionmentioning
confidence: 99%